The Development of Criteria for the Selection of Chinese Peer Educators in HIV Management: A Delphi Study - Yan Qiu; Jiayin Shen; Hongzhou Lu (Scientifica)
To develop an expert consensus opinion of the criteria for selection of peer educator for HIV/AIDS care program, twenty experts were invited to complete a two-round Delphi consultation. Response rates of the panelists for the first and second rounds were both 100%, and the authority coefficient of the experts was 0.75. Experts achieved consensus on a total of nine items (75%) on completion of the study. The Precedence Chart Method was used to calculate the weight of each indicator, and then a priority list was generated accordingly. This study provides the initial selection criteria for HIV/AIDS peer educators in Shanghai as well as in China.